Pengaruh karakteristik CEO terhadap kinerja bagian keuangan (akuntan) perusahaan - Adanan Silaban; Manatap Berliana Lumban Gaol (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The company is one of the sectors that can be used to improve the Indonesian economy. Unfortunately, not all companies are in good health, especially in the financial sector. In fact, finance is important for the sustainability of the company's operations. The company's finances are held by an accountant who is under the authority of the CEO. For this reason, researchers want to conduct research on